High-Resolution Analysis of Ionomer Loss in Catalytic Layers after Operation. Issue 6 (15th March 2018) - Morawietz, T.; Handl, M.; Oldani, C.; Gazdzicki, P.; Hunger, Jürgen; Wilhelm, Florian; Blake, John; Friedrich, K. A.; Hiesgen, R.
Abstract : The function of catalytic layers in fuel cells and electrolyzers depends on the properties of the ionically conductive phase, which are most commonly perfluorinated ionomers based on Nafion and Aquivion. An analysis by atomic force microscopy reveals that the ultrathin ionomer films around Pt/C agglomerates have a thickness distribution ranging from 3.5 nm to 20 nm. Their conductivity and gas permeation properties determine the fuel cell performance to a large extend. For electrodes in Aquivion-based membrane-electrode-assemblies operation-induced structure changes were investigated by means of material- and conductivity-sensitive atomic force microscopy, infrared spectroscopy and electron-dispersive X-ray analysis. The observed thinning of the ultrathin ionomer films was mainly caused by polymer degradation deduced from reduced swelling after long-time operation and a significant loss of ionomer with operation time detected by infrared spectroscopy. From the linear thickness increase of the ultrathin films with rising humidity, a mainly layered structure of the ionomer was deduced. An influence of thickness of such ultrathin ionomer films on fuel cell lifetime was found by analysis of differently prepared membrane-electrode-assemblies, where a linear increase of irreversible degradation rate with ionomer film thickness in the electrodes of unused membrane-electrode-assemblies was found.